Community Empowerment: Optimizing Capital Management And Market Access For Sikat Stone Ceramic Artisans: English - Sedana Putra P, Komang Widhya; Maitri, Wayan Sri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The community service was a program inspired by the problems of Sikat stone craftsmen in capital management, access to markets, and knowledge of business management. This program adopted a participatory approach in order to enhance the skills of the craftsmen in capital management and access to the market, including the implementation of sustainable economic principles. The main objectives of the program were improved capital management, increased market access through digitized marketing, and the introduction of the concept of sustainability to the craftsmen. Among the major issues analyzed were poor capital management, limited market access, and lack of knowledge in sustainable economics. The result of such a process is that, so far, 80% of the artisans have been able to implement better financial recording systems; 70% have begun to use digital marketing, realizing a 30% increase in sales within the first three months of the exercise. Also, 60% of the artisans so far have pledged to shift to more environmentally friendly raw materials. It has, therefore, brought about changes in capital management, market access, and awareness of sustainable practices among the sikat stone craftsmen. These deeds, while perhaps holding a great potential for independent and sustainable business growth, have their drawbacks; there is a dire need for continuous mentoring and monitoring if these changes are to persist.